Робототехнічні системи та їх застосування для пошуку вибухонебезпечних предметів - Шафоростов, Д. Д. (ХНУРЕ, 2022)
The aim of the work is to study current issues related to the creation of robotic systems and complexes (RSC) of military (dual) purpose for humanitarian demining. The use of the RSC in the humanitarian demining system is due to the efforts of all countries to save lives, both in combat and in the process of humanitarian demining of areas contaminated with explosives objects (EO). The main tasks in the problem of humanitarian demining are the search and identification of EO in accordance with their unmasking features. Creating a RSC to search for EO will reduce the cost of searching for and identifying it, thanks to the early marking of EO-contaminated areas to solve the problem of civilian casualties, reduce military losses.
Keywords: robotic systems and complexes; explosives objects; humanitarian demining